Ketimpangan Gaji Dosen dan Dampaknya pada Kinerja Perguruan Tinggi Swasta (PTS) di Indonesia - Muhammad Eko Purwanto; Muannif Ridwan (Journal of Education and Culture, 2026)
The wage disparity between lecturers in public and private universities in Indonesia has become a significant issue, affecting the quality of higher education. Lecturers in private universities often receive lower wages despite having qualifications comparable to those in public universities. This disparity impacts their welfare, reduces motivation, and affects their performance in teaching, research, and community service. Additionally, the excessive workload on lecturers in private universities, with many tasks to complete without adequate compensation, contributes to stress and fatigue, which diminishes their effectiveness in carrying out academic duties. This decline in performance influences learning outcomes and the overall academic quality. The managerial factors, such as inadequate human resource management, also pose a major problem. Private universities lacking supportive policies, such as career development programs for lecturers and sufficient incentives, struggle to improve the quality of education. Therefore, improvements in managerial policies and lecturer management in private universities are crucial to enhancing lecturer welfare and the quality of higher education in Indonesia.